Proportional Principles with the Decomposition of Two Floor Slabs in the Southern Chancel of Milutin’s Church at Hilandar - Radojević, Milan A.; Radojević, Aleksandar M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The paper examines the proportional principles applied to the compositional design of the floor in the southern chancel of Milutinʼs church at Hilandar. The aim of the paper is to demonstrate the establishment of relations between proportional logic and compositional structure, as manifested through geometric forms. Two floor slabs are selected and analyzed with regard to the use of various geometric shapes, including the square, circle, triangle, and octagon. The initial hypothesis posits that the application of these geometric shapes evokes a structural configuration grounded in the geometric regularity of square division. This assumption was confirmed through procedures of proportional analysis and geometric decomposition applied to both floor slabs. By means of proportional analysis, decomposition, and comparative analysis—identifying analogies and distinctions, it is concluded that the ornamental designs on the floor tiles forming the two slabs exhibit complete geometric regularity and harmonic balance, indicating the exceptional craftsmanship of the period’s builders and a confluence of diverse influences and skills.